2016
DOI: 10.7836/kses.2016.36.4.041
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of PV module under the Partial Shading Condition and with a Failure of Bypass Diode with Short

Abstract: :A bypass diode is connected in parallel to solar cells with opposite polarity. The advantage of using the bypass diode is circumvented a destructive efforts of hot-spot heating in the photovoltaic(PV) module. In addition, it is possible to reduce a energy loss under the partial shading on the PV module. This paper presents a characteristic of photovoltaic module under partial shading condition and with defective bypass diode by using the experimental data. The results of field testing for each photovoltaic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…From the measured temperature data, it was confirmed that the temperature inside the junction box of the PV module operating normally was distributed in the range of 38 to 72 • C based on the maximum value. It can be assumed that the temperature inside the junction box was higher than when shading occurred, during which the bypass diode conducts forward voltage, or the bypass diode fails [30]. Moreover, the inside of the junction box was exposed to temperatures of over 60 • C for more than 90 h in high ambient temperature (June to September), which may have caused problems to the bypass diode.…”
Section: Temperature In the Junction Box Of A C-si Pv Module Installementioning
confidence: 99%
“…From the measured temperature data, it was confirmed that the temperature inside the junction box of the PV module operating normally was distributed in the range of 38 to 72 • C based on the maximum value. It can be assumed that the temperature inside the junction box was higher than when shading occurred, during which the bypass diode conducts forward voltage, or the bypass diode fails [30]. Moreover, the inside of the junction box was exposed to temperatures of over 60 • C for more than 90 h in high ambient temperature (June to September), which may have caused problems to the bypass diode.…”
Section: Temperature In the Junction Box Of A C-si Pv Module Installementioning
confidence: 99%
“…The failure of the bypass diodes causes them to lose their reverse characteristics, so when a forward voltage is applied to the PV module (bypass diodes in a reverse state), current can flow into the failure of the bypass diode. At the same time, the solar cells connected to the fault bypass diode constitute a short-circuit condition, and their generated voltage is about 0 V, which reduces the overall voltage of the PV module [21]. The experimental results show that, if all of the bypass diodes in the PV module fail, the open-circuit voltage is reduced by up to 90%, so the reverse current will likely flow into PV modules with the failure of the bypass diode.…”
Section: The Failure Of Bypass Diodesmentioning
confidence: 99%